Study of the Spatial Heterogeneity of the Economy of Russian Regions - Lyudmila V. OVESHNIKOVA; Elena V. SIBIRSKAYA; Olga G. LEBEDINSKAYA; Alexander G. TIMOFEEV (Communications of International Proceedings, 2021)
This paper analyzes the indicators of the economic efficiency of the Russian economy, including in the regional context. The system of indicators for the study was compiled in such a way that it was possible to characterize the level of innovative and scientific and technological development, the quality of labor resources, the state of fixed assets and production volumes. Analysis of indicators in the regional context showed a high level of differentiation of Russian regions in terms of the level of economic development and efficiency of the economy of the constituent entities of the Russian Federation. Leading regions, effectively developing and outsider regions with a low level of economic development are identified. To increase the level of efficiency of the national economy, the directions for solving social and economic problems in outsider regions, based on the policy of forming a single innovation space of the Russian economy, have been determined.
Keywords: Differentiation; Heterogeneity; Economic Efficiency; Regional Economy; Leading Regions; Outsider Regions.